Chapter Considerazioni su arte francese e arte italiana: da Luigi XII e Francesco I alla Maison de Gondi di Saint-Cloud e agli Orléans - Pelliciari, Medardo (Studi e saggi, 2020)
The paper retraces the relationship between Italian and French art from the late 15th to the early 18th century, by focusing on some relevant episodes related especially to the Pio di Savoia and the Medici families and their connections with members of the French court.